Beyond boundaries: unraveling innovative approaches to combat bone-metastatic cancers - Lan, Huanrong; Wu, Bo; Jin, Ketao; Chen, Yefeng (Frontiers in Endocrinology, 2024)
Evidence demonstrated that bones, liver, and lungs are the most common metastasis sites in some human malignancies, especially in prostate and breast cancers. Bone is the third most frequent target for spreading tumor cells among these organs and tissues. Patients with bone-metastatic cancers face a grim prognosis characterized by short median survival time. Current treatments have proven insufficient, as they can only inhibit metastasis or tumor progression within the bone tissues rather than providing a curative solution. Gaining a more profound comprehension of the interplay between tumor cells and the bone microenvironment (BME) is of utmost importance in tackling this issue. This knowledge will pave the way for developing innovative diagnostic and therapeutic approaches. This review summarizes the mechanisms underlying bone metastasis and discusses the clinical aspects of this pathologic condition. Additionally, it highlights emerging therapeutic interventions aimed at enhancing the quality of life for patients affected by bone-metastatic cancers. By synthesizing current research, this review seeks to shed light on the complexities of bone metastasis and offer insights for future advancements in patient care.